2021
DOI: 10.1111/gcb.15874
|View full text |Cite
|
Sign up to set email alerts
|

Climate change may interact with nitrogen fertilizer management leading to different ammonia loss in China’s croplands

Abstract: Despite research into the response of ammonia (NH3) volatilization in farmland to various meteorological factors, the potential impact of future climate change on NH3 volatilization is not fully understood. Based on a database consisting of 1063 observations across China, nonlinear NH3 models considering crop type, meteorological, soil and management variables were established via four machine learning methods, including support vector machine, multi‐layer perceptron, gradient boosting machine and random fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Four RF models were used to identify explanatory variables that are most important to variations in global effects of non-continuous flooding practices on CH 4 emissions, N 2 O emissions, IRR, and rice yield, respectively. Similar models have been widely used for relative importance assessment (Xu et al, 2021), by measuring the increase in the out-of-bag (OOB) error when the variable was randomly permuted, while keeping all the other variables unchanged. The larger the increase in the OOB error the more important is the role of the corresponding variable.…”
Section: Relative Importance Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Four RF models were used to identify explanatory variables that are most important to variations in global effects of non-continuous flooding practices on CH 4 emissions, N 2 O emissions, IRR, and rice yield, respectively. Similar models have been widely used for relative importance assessment (Xu et al, 2021), by measuring the increase in the out-of-bag (OOB) error when the variable was randomly permuted, while keeping all the other variables unchanged. The larger the increase in the OOB error the more important is the role of the corresponding variable.…”
Section: Relative Importance Assessmentmentioning
confidence: 99%
“…Its built‐in variable importance assessment and error monitoring makes it robust in identifying the functional form of the relationships and provided more accurate predictions (Yin et al, 2021). It can also capture complex nonlinear relationships between predictors and outputs, and its predictive power in representing climatic or management effects has been demonstrated in a wide range of studies, with the advantage of higher computational efficiency and being robust to overfitting and noise data (Liu et al, 2019a; Terrer et al, 2019; Xu et al, 2021; Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The persistent yield gap between potential and actual yield is an important issue to be solved for global food production, especially in low‐ and middle‐inputs regions (Ray et al., 2012). Adaptation strategies, like optimized irrigation and N fertilization strategies, determine the potential for closing yield gaps, increasing yield and resource use efficiency, and reducing agricultural pollution (Horton et al., 2021; Liu, Yang, Folberth, et al., 2018; Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation strategies have been proven to be effective to increase both crop yield and resource use efficiency in changing environments (Lee et al., 2014; Xu et al., 2021). Previous studies, based on statistics, field experiments, and modelling, have shown that regulated deficit irrigation could achieve the win‐win of crop yield and irrigation water productivity (WP I ) (Du et al., 2015; Kang et al., 2017; Mansouri‐Far et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of climate change on N dynamics in CZs should also be considered. Drought and rising temperatures during crop growth periods would lead to increased ammonia volatilization on national scales and different responses on regional scales (Xu et al, 2021). Moreover, the impact of climate change on microbial communities and functions in CZs should also be evaluated.…”
Section: The Future Work Toward Sustainabilitymentioning
confidence: 99%